Implementasi Komunikasi Islam Qaulan Maysura dalam Membentuk Kesantunan Berbahasa Di Bank Sumut - Afifi Lubis; Azhar (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2024)
This research aims to determine the implementation of Islamic communication Qaulan Maysura in forming language politeness at Bank Sumut. This research applies a descriptive qualitative method with a phenomenological approach in order to identify problems through direct observation of the natural conditions of the research object. The data sources for this research consist of primary data obtained through observation and secondary data sourced from literature reviews. The data analysis process involves reducing findings, presenting descriptively, and verifying to support the validity of research results. This approach is designed to provide an in-depth understanding of the phenomenon under study and has the potential to contribute to the development of theoretical or practical understanding in the context of the research being carried out. The results of this research show that Bank Sumut applies the Qaulan Maysura concept, teaching employees to communicate with words of wisdom, politeness and kindness. Politeness includes clarity of information, respect and gentleness in interactions with customers. This approach is not only a communication strategy, but also an effort to strengthen customer trust and loyalty, making Bank Sumut a partner that cares about the human aspect in every interaction.